2012
DOI: 10.1016/j.rbmo.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Screening of sperm velocity by fluid mechanical characteristics of a cyclo-olefin polymer microfluidic sperm-sorting device

Abstract: The microfluidic sperm-sorting (MFSS) device is a promising advancement for assisted reproductive technology. Previously, poly(dimethylsiloxiane) and quartz MFSS devices were developed and used for intracytoplasmic sperm injection. However, these disposable devices were not clinically suitable for assisted reproduction, so a cyclo-olefin polymer MFSS (COP-MFSS) device was developed. By micromachining, two microfluidic channels with different heights and widths (chip A: 0.3 × 0.5 mm; chip B: 0.1 × 0.6 mm) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 15 publications
0
25
0
1
Order By: Relevance
“…Among LOC devices, microfluidic sperm sorting (MFSS) chips have been developed and marketed for motile sperm sorting and use two gravity-driven laminar flows across a microfluidic channel of 50-200 µm [52][53][54][55][56][57][58][59][60][61]. Fluids flowing through the semen inlet (A) and the medium inlet (B) move parallel to each other and exit through respective outlets (A→D and B→C) [53].…”
Section: Microfluidic Channel-based Devices For Semen Diagnoses and Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Among LOC devices, microfluidic sperm sorting (MFSS) chips have been developed and marketed for motile sperm sorting and use two gravity-driven laminar flows across a microfluidic channel of 50-200 µm [52][53][54][55][56][57][58][59][60][61]. Fluids flowing through the semen inlet (A) and the medium inlet (B) move parallel to each other and exit through respective outlets (A→D and B→C) [53].…”
Section: Microfluidic Channel-based Devices For Semen Diagnoses and Mmentioning
confidence: 99%
“…Sperm are then sorted on the basis of their ability to swim across the streamline into the medium stream, and only motile sperm are recovered from outlet C. Using MFSS devices, embryologists can perform a 1-step sorting protocol without centrifugation, and processing can be completed within 30 min [40,[57][58][59][60][61]. Moreover, DNA fragmentation was reduced and sperm with high linear velocities (LV) were effectively sorted [58,60]. Hence, commercialized MFSS devices can be used with clinical semen processing protocols for efficient ICSI and IVF.…”
Section: Microfluidic Channel-based Devices For Semen Diagnoses and Mmentioning
confidence: 99%
“…Within the last decade, studies using PDMS microfluidic channels or funnels have suggested novel solutions for oocyte manipulation, sperm sorting, and embryo culture . Microfluidic systems that mimic oviductal structures and functions for use in RT are divided into those used for sperm motility control or monitoring [50][51][52][53][54][55][56][57][58][59][60], regulation of chemical gradients for in vitro fertilization and embryo culture [61][62][63][64][65][66][67][68][69], and applying mechanical stimuli to the developing embryo [70][71][72][73][74]. Although the unique characteristics of elastomers have been exploited for microstructure fabrication and/or micro-pumping, mechanical deformation of the elastomer membrane has not been used to produce new devices for RT.…”
Section: Microfluidic Channels To Handle Sperm and Embryosmentioning
confidence: 99%
“…Some procedures may take up to 2 h for semen processing by conventional protocols, such as density gradient centrifugation and subsequent swim-up [75]. To reduce treatment times and physical damage induced by centrifugation, microfluidic sperm sorting (MFSS) chip devices have been developed for selecting motile sperm for use in ART [50][51][52][53][54][55]. As shown in Figure 3A, two gravity-driven laminar flows within the microfluidic channel are important for sperm selection.…”
Section: Elastomer Chip Device For Sperm Sortingmentioning
confidence: 99%
See 1 more Smart Citation